2020
DOI: 10.1097/md.0000000000020836
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ipratropium bromide on the occurrence of postoperative respiratory complications in craniectomy patients with COPD

Abstract: Introduction: Postoperative pulmonary complications (PPCs) are common and associated with increased morbidity, mortality, and medical cost. They are gaining increasing concerns among patients receiving neurological surgery. Chronic obstructive pulmonary disease (COPD) affect a large section of whole population and is also one of the risk factors of PPCs in the perioperative setting. Ipratropium bromide is the inhalation solution for the treatment of COPD. Studies showed the perioperative nebulizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Numata T et al (15) have demonstrated that long-acting anticholinergic drugs and long-acting β2 receptor agonists can effectively reduce the rate of postoperative pulmonary complications in patients with COPD. Du Z et al (16) have further demonstrated that perioperative aerosol inhalation of ipratropium bromide can reduce the incidence of postoperative pneumonia in COPD patients undergoing thoracic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numata T et al (15) have demonstrated that long-acting anticholinergic drugs and long-acting β2 receptor agonists can effectively reduce the rate of postoperative pulmonary complications in patients with COPD. Du Z et al (16) have further demonstrated that perioperative aerosol inhalation of ipratropium bromide can reduce the incidence of postoperative pneumonia in COPD patients undergoing thoracic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary chronic inflammation in patients with COPD is a characteristic pathological change that will continue to destroy the alveolar wall septum and result in pulmonary interstitial fibrosis (9,14). Some previous studies have confirmed that preoperative treatment for COPD can reduce the incidence of postoperative pneumonia (15,16). Numata T et al (15) have demonstrated that long-acting anticholinergic drugs and long-acting β2 receptor agonists can effectively reduce the rate of postoperative pulmonary complications in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Such factors may precipitate impaired lung ventilation functionality and damage to the mucociliary mechanism responsible for clearing pathogens from the airway [46][47][48][49] . Some studies have a rmed the e cacy of interventions aimed at curtailing the incidence of postoperative pneumonia in COPD patients 50,51 .Key interventions to diminish the risk of postoperative pneumonia include the preoperative prescription of long-acting anticholinergic drugs and β2 receptor blockers, intraoperative inhalation of ipratropium bromide, and implementing the use of an incentive spirometer postoperatively along with elevation of the bed head and upkeeping oral hygiene with chlorhexidine [50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
“…However, those abovementioned treatments can only play an auxiliary role but have no significant improvement on the patient's lung function, thereby requiring combination therapy for the symptoms [ 12 , 13 ]. Ipratropium bromide (IB) is a bronchodilator that can directly act on M receptors in the bronchial smooth muscle to inhibit airway remodeling and improve lung function [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%